2017
DOI: 10.1073/pnas.1707120114
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A forms stable oligomers that disrupt vesicles at lysosomal pH and contribute to the pathogenesis of reactive amyloidosis

Abstract: Serum amyloid A (SAA) is an acute-phase plasma protein that functions in innate immunity and lipid homeostasis. SAA is a protein precursor of reactive AA amyloidosis, the major complication of chronic inflammation and one of the most common human systemic amyloid diseases worldwide. Most circulating SAA is protected from proteolysis and misfolding by binding to plasma high-density lipoproteins. However, unbound soluble SAA is intrinsically disordered and is either rapidly degraded or forms amyloid in a lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 47 publications
2
50
0
2
Order By: Relevance
“…In addition to the inducible feature, our approach allows for the production of lipid-free or lipid-poor SAA1 proteins that are crucial to studies of its interaction with cell surface receptors and pathogen-derived molecules such as LPS. The forms and sites of SAA production are important to experimental design, given that SAA in lipid-bound and lipid-free forms may produce different biological functions [26,27]. Using the SAA1 transgenic mice, we report for the first time that acute-phase SAA1 offers partial protection against LPS-induced inflammation and acute lung injury through direct binding to LPS and promotion of its clearance.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to the inducible feature, our approach allows for the production of lipid-free or lipid-poor SAA1 proteins that are crucial to studies of its interaction with cell surface receptors and pathogen-derived molecules such as LPS. The forms and sites of SAA production are important to experimental design, given that SAA in lipid-bound and lipid-free forms may produce different biological functions [26,27]. Using the SAA1 transgenic mice, we report for the first time that acute-phase SAA1 offers partial protection against LPS-induced inflammation and acute lung injury through direct binding to LPS and promotion of its clearance.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the inducible feature, our approach allows for the production of lipid‐free or lipid‐poor SAA1 proteins that are crucial to studies of its interaction with cell surface receptors and pathogen‐derived molecules such as LPS. The forms and sites of SAA production are important to experimental design, given that SAA in lipid‐bound and lipid‐free forms may produce different biological functions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global amyloidosis epidemic is a major complex combination of many diseases involving chronic inflammatory and misfolding of proteins that are characterized by the accumulation of amyloid-plaques and neurofibrillary tangles in tissues and organs [27][28][29]. Although there have been breakthroughs related to the structure and molecular mechanisms of amyloid proteins [30][31][32], the pathogenic mechanism of amyloidosis is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on murine lipid free SAA, it was shown that SAA forms unusually stable soluble oligomers at pH 3.5-4.5 that may escape from lysosomal degradation and contribute to the SAA accumulation in lysosomes and eventually participate in the formation of intracellular amyloid. In addition, lipid vesicles accelerate the conversion of these oligomers from a-helix to b-sheet which involves structural remodelling of both protein and lipid as well as disruption of lipid membrane [45]. When SAA concentration is elevated, it dissociates from HDL and consequently a fraction of SAA might circulate in plasma as lipid-free SAA [46].…”
Section: Discussionmentioning
confidence: 99%